Plasmonic optical fiber for bacteria manipulation—characterization and visualization of accumulation behavior under plasmo-thermal trapping - Kim,J; Yeatman,E; Thompson,A (Biomedical Optics Express, 2021)
In this article, we demonstrate a plasmo-thermal bacterial accumulation effect usinga miniature plasmonic optical fiber. Combined action of far-field convection and a near-fieldtrapping force (referred to as thermophoresis)—induced by highly localized plasmonicheating—enabled large-area accumulation of Escherichia coli. The estimated thermophoretictrapping force agreed with previous reports, and we applied speckle imaging analysis to mapthe in-plane bacterial velocities over large areas. This is the first time that spatial mapping ofbacterial velocities has been achieved in this setting. Thus, this analysis technique providesopportunities to better understand this phenomenon and to drive it towards in vivo applications.